2014
DOI: 10.1177/0004563214545346
|View full text |Cite
|
Sign up to set email alerts
|

Variation of betaine, N,N-dimethylglycine, choline, glycerophosphorylcholine, taurine and trimethylamine-N-oxide in the plasma and urine of overweight people with type 2 diabetes over a two-year period

Abstract: Background: Plasma betaine concentrations and urinary betaine excretions have high test-retest reliability. Abnormal betaine excretion is common in diabetes. We aimed to confirm the individuality of plasma betaine and urinary betaine excretion in an overweight population with type 2 diabetes and compare this with the individuality of other osmolytes, onecarbon metabolites and trimethylamine-N-oxide (TMAO), thus assessing their potential usefulness as disease markers. Methods: Urine and plasma were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 26 publications
4
44
0
1
Order By: Relevance
“…48, 49 Current data supports the conclusion that the major origin of inter-individual differences is due to the large diversity of gut microbiota and community structure among individuals. Recent observations indicate that overall gut microbial community structure is modulated by long-term dietary exposure.…”
Section: Pathogenic Mechanism and Therapeutic Implications Of Tmao Insupporting
confidence: 66%
“…48, 49 Current data supports the conclusion that the major origin of inter-individual differences is due to the large diversity of gut microbiota and community structure among individuals. Recent observations indicate that overall gut microbial community structure is modulated by long-term dietary exposure.…”
Section: Pathogenic Mechanism and Therapeutic Implications Of Tmao Insupporting
confidence: 66%
“…On the other hand, it has been found that diabetic patients treated with metformin showed decreased glucose but increased plasma TMAO compared to untreated ones [72]. Other studies suggest a low diagnostic value of TMAO measurements in obese diabetic patients due to high variability of plasma TMAO concentrations [73]. To our knowledge, the level of plasma TMAO in diabetic laboratory animals has not yet been reported.…”
Section: Diabetesmentioning
confidence: 84%
“…While the association between TMAO and atherosclerosis initially reported by Tang et al. (2013) is now accepted (Bennett et al., 2013, Koeth et al., 2013, Koeth et al., 2014, Ussher et al., 2013, Wang et al., 2011b), the roles played by TMAO in glucose homeostasis are less clear (Bai et al., 1998, Gao et al., 2014, Lever et al., 2014, McEntyre et al., 2015). …”
Section: Discussionmentioning
confidence: 99%